Penentuan Prioritas Dan Kelayakan Finansial Dalam Investasi Magnetic Resonance Imaging (MRI) - Widada Widada (Universitas Muhammadiyah Sumatera Utara, 2020)
The present study aimed to analyze the determination of MRI priorities and financial feasibility. This study applied a mixed method approach, which is a combination of qualitative and quantitative approaches. This studi used primary and secondary data. Primary data used are the opinions of stakeholders in selecting criteria and alternative MRI collected directly from selected stakeholders. Primary data was obtained through Focus Group Discussion (FGD) with stakeholder data sources. Secondary data includes MRI prices and specifications on the LKPP e-catalog website, financial reports, data on MRI examinations, and patient diagnostic data. Data analysis used Analytical Hierarchy Process (AHP) and investment feasibility analysis. AHP analysis results explain the priority order of MRI criteria are software, hardware, accessories and prices, while alternative MRI priorities are GE 16-CHANNEL, Philips 1.5T, Siemens 1.5T, and Canon 1.5T. MRI investments with the GE brand are declared feasible because they have an IRR value above the applied discount factor (16%), a positive NPV value, a Payback Period value of less than 6 years, a Benefit of Cost ratio> 1, and a PV of proceeds / Net value investment above 1.